2006
DOI: 10.2306/scienceasia1513-1874.2006.32.127
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: An epidemiologic study of methicillin-resistant Staphylococcus aureus (MRSA) was conducted by antibiotype, coagulase gene typing and polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) analysis. A total of 129 MRSA strains were isolated from 17 hospitals in the regions of the central, northern, northeastern and eastern Thailand during November 2003 -March 2004. Antimicrobial susceptibility testing with a panel of 10 antimicrobial agents showed 9 different antibiotypes. The antibiotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 11 publications
2
2
0
Order By: Relevance
“…There were 89 MRSA strains isolated from burns patients with 10 coa genes identified by multiplex PCR, similar to the results of Afrogh et al [10], who showed 9 different patterns of coa genes among staff nose, and patients’ clinical samples in Iran. The same results were reported by Janwithayanuchit et al [27] from Thailand, and Omar et al [28] from Egypt. Our study has reported that types III, II, I and VIII were the most common, and accounted for 47.2%, 14.6%, 10.1% and 10.1% of the isolates, respectively.…”
Section: Discussionsupporting
confidence: 89%
“…There were 89 MRSA strains isolated from burns patients with 10 coa genes identified by multiplex PCR, similar to the results of Afrogh et al [10], who showed 9 different patterns of coa genes among staff nose, and patients’ clinical samples in Iran. The same results were reported by Janwithayanuchit et al [27] from Thailand, and Omar et al [28] from Egypt. Our study has reported that types III, II, I and VIII were the most common, and accounted for 47.2%, 14.6%, 10.1% and 10.1% of the isolates, respectively.…”
Section: Discussionsupporting
confidence: 89%
“…In a research involving 157 S. aureus strains from clinical specimens, nine different patterns of coa gene were detected (Afrough et al, 2013). These findings were confirmed by results in Thailand (Janwithayanuchit et al, 2006) and Egypt (Omar et al, 2014) reported previously. Genetic variability in coa gene among studied isolates indicated that it could not be a predictor for specific iMLSB S. aureus strains.…”
Section: Discussionsupporting
confidence: 83%
“…Variations (polymorphism) in the genomic sequences are not uncommon in S. aureus, even highly conserved and widely used species specific markers like coagulase (coa), Staphylococcal Protein A (spa) genes have shown polymorphisms. Variations in the sequence of the coa and spa genes and the hyper variable region adjacent to the mecA gene, have been the basis for the most widely used forms of PCR typing of MRSA [26][27][28]. Further, it is also known that sequence variations culminate in changes in virulence properties of S. aureus which influence clinical disease manifestations in humans [29].…”
Section: Discussionmentioning
confidence: 99%